Pengaruh Lingkungan Kerja, Budaya Organisasi dan Beban Kerja Terhadap Kepuasan Kerja Dan Kinerja Karyawan BPJS Kesehatan Cabang Muaro Bungo; The Effect Of Work Environment, Organizational Culture And Workload on Job Satisfaction and Employees Performance of BPJS Health Branch Muaro Bungo - Kurniawan, Kurniawan (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2022)
There are few serious problems faced by BPJS Kesehatan such as inaccuracy in member’s data management, complicated system, mistreatment toward BPJS patients, and patients’ rejection in several hospitals for various reasons. These problems could be analyzed by scrutinizing the employee work satisfaction and performance which are affected by work environment, organization culture, and employee workload. This study aimed to determine the effect of the work environment, organizational culture and workload on job satisfaction and employee performance of BPJS Kesehatan Muara Bungo branch in 2020. This study was conducted using a quantitative statistical approach and collecting research data using questionnaire. The population in this study were all employees of BPJS Kesehatan Muara Bungo Branch Office, totaling 105 people and all of them were assigned as research respondents. The dependent variable was employee performance and job satisfaction, while the use of the independent variable consisted of the work environment, organizational culture, and workload. Structural Equation Model (SEM) was applied to analyze data for answering the research hypothesis. The findings in this study proved that the work environment, workload, and organizational culture affected on job satisfaction. Workload and organizational culture variables affected employee performance while the work environment variable did not affect performance. The test results of job satisfaction variables were known to have an influence on employee performance variables.